The effect of BLA GABA(A) receptors in anxiolytic-like effect and aversive memory deficit induced by ACPA - Kangarlu-Haghighi, Katayoon (EXCLI J, 2015)
The roles of GABAergic receptors of the Basolateral amygdala (BLA) in the cannabinoid CB1 receptor agonist (arachydonilcyclopropylamide; ACPA)-induced anxiolytic-like effect and aversive memory deficit in adult male mice were examined in elevated plus-maze task. Results showed that pre-test intra-peritoneal injection of ACPA induced anxiolytic-like effect (at dose of 0.05 mg/kg) and aversive memory deficit (at doses of 0.025 and 0.05 mg/kg). The results revealed that Pre-test intra-BLA infusion of muscimol (GABA(A) receptor agonist; at doses of 0.1 and 0.2 µg/mouse) or bicuculline (GABA(A) receptor antagonist; at all doses) impaired and did not alter aversive memory, respectively. All previous GABA agents did not have any effects on anxiety-like behaviors. Interestingly, pretreatment with a sub-threshold dose of muscimol (0.025 µg/mouse) and bicuculline (0.025 µg/mouse) did not alter anxiolytic-like behaviors induced by ACPA, while both drugs restored ACPA-induced amnesia. Moreover, muscimol or bicuculline increased and decreased ACPA-induced locomotor activity, respectively. Finally the data may indicate that BLA GABA(A )receptors have critical and different roles in anxiolytic-like effect, aversive memory deficit and locomotor activity induced by ACPA.